Factors Influencing the Incident of Acute Respiratory Tract Infections in Children Aged 12-59 Months in Wallandimu East Nusa Tenggara - Novita Ana Anggraini; Rahmania Ambarika; Natalia Ningsi Katupu (Journal Of Nursing Practice, 2024)
Background: Acute Respiratory Infection Disease is one of the highest causes of morbidity and mortality in children under five in Indonesia, especially in East Nusa Tenggara. The implementation of the ISPA disease control program focuses on finding and treating sufferers as early as possible by involving the active role of cadres, integrated health service support and referrals to related health facilities, however, these control efforts have not shown significant results. Purpose: The aim of this study was to determine the factors that influence the incidence of Acute Respiratory Infection Disease  in children aged 12-59 months in the Wallandimu Community Health Center working area. Method: This research uses an analytical research design with a cross sectional approach. The population in this study were toddlers aged 12-59 months in the Wallandimu health center working area and the sample in this study was 30 toddlers. The sampling technique in this research was simple random sampling. The Chi-Square statistical test was used to determine the relationship between variables. Results: The results of the research from 18 respondents showed complete immunization status (76.7%), poor nutritional status (60.0%), and insufficient knowledge (56,7%) regarding the incidence of ISPA in the Wallandimu Health Center working area. The results of bivariate analysis showed no influence between immunization status and the incidence of ISPA (p= 0.896 > 0.05), there was an influence between nutritional status and the incidence of ISPA (p= 0.007 < 0.05), there was an influence between maternal knowledge and the incidence of ISPA (p = 0.010 < 0.05). Conclusion: It is hoped that the Wallandimu Community Health Center will further improve its health programs, especially the Acute Respiratory Infection Disease control program for toddlers and provide education regarding maternal knowledge and the dangers of malnutrition for toddlers, so that the incidence of Acute Respiratory Infection Disease in children aged 12-59 months will decrease.